Cultural Phenomena Believed to Be Associated With Orthorexia Nervosa – Opinion Study in Dutch Health Professionals - Syurina, Elena V.; Bood, Zarah M.; Ryman, Frida V. M.; Muftugil-Yalcin, Seda (Frontiers in Psychology, 2018)
Orthorexia Nervosa (ON) is a newly coined eating pattern which disproportionately affects Western countries. Research on the matter is scarce. This study aimed to investigate how the Dutch (mental) health professionals evaluate the influence of “Western culture” on the development of ON. This mixed methods study included interviews (n = 15) and a questionnaire (n = 157). The extent of influence of the “Western culture” was suggested to be quite high, with a score of 74 out of 100. The factors believed to affect Orthorexia included societal transitions (epidemiological and welfare) and cultural ideas (body ideal and control over life) which, in turn, are influenced by the internet and media. In addition, it was noted that ON is unique among the eating disorders since it does not carry the negative connotations of anorexia or obesity associated with “losing control.” The findings suggest that “Western culture” contributes to the establishment of a high-risk environment for the development of behaviors associated with ON.